Formulasi Sabun Mandi Transparan Halal Ekstrak Rosella dengan Dietanolamida sebagai Surfaktan - Fina Uzwatania; Aditia Ginantaka; Deuis Nur Hasanah (JURNAL AGROINDUSTRI HALAL, 2020)
Rosella flower petals contain anthocyanin dyes which can be used as natural dyes. One of the uses of rosella is to add it to transparent bath soap with dietanolamide as surfactant. Dietanolamide is a surfactant that can function to increase the stability of foam in transparent soap. This study aims to determine the best formulation, characteristics and consumer acceptance of transparent soap with rosella extract with dietanolamide as surfactant. The treatment given in this study is the concentraction of rosella extract by 1%, 2%, and 3%. Whereas for DEA is 1% and 3%. Observations made on transparent soap include physicochemical tests of soap, organoleptic tests, and statistical tests with ANOVA variance. The results of the analysis show that all formulations do not meet the requirements of SNI 06-3532-1994. Except for pH, foam stability, and emulsion stability. Organoleptic results (shape, color, transparency, lots of foam, and impression of fatigue) showed that panelists liked formulation 2 with the addition of 2% roselle extract and 1% dietanolamide.Keywords: Transparent soap, rosella extract, dietanolamide